THROMBOCYTOPENIC PURPURA - VILLASENOR BAEZ, JOSE (Hospital General, CD MEXICO, DF, MEX, 1976)
The results of a comparative study of phthalylsulfacetamide and of phthalylsufathiazol indicate that, because of lesser toxicity and the possibility of obtaining large concns of sulfonamides on the intestinal walls, the 1st substance possesses advantages
CLIN GENET
Keywords: THROMBOCYTOPENIC PURPURA; MULTIDISCIPLINARIA; BIOLOGIA HUMANA; FISIOLOGIA HUMANA